A black box assessment of institutional quality: the challenge of evaluating lobbying transparency. (4th May 2023) - Laboutková, Šárka; Vymětal, Petr
ABSTRACT: Lobbying is considered to be a legitimate feature of democratic systems, but a question arises concerning the methods used to influence decision-making processes in these systems; the behaviour of lobbyists and decision-makers can be non-transparent, and it unfairly influences political processes. These accompanying phenomena significantly affect institutional quality. In this paper, we define the link between transparent decision making and a transparent lobbying environment, we provide a new set of indicators for a more precise assessment of the transparent lobbying environment in Catalogue of Transparent Lobbying Environment and we demonstrate the differences between our approach of evaluating transparent lobbying and existing methods for six CEE countries empirically. Finally, we address institutional quality and its evaluation in connection with transparent lobbying and demonstrates the potential of the catalogue. We argue that a transparent lobbying environment should be analyzed in the broader context of the decision-making process and is essential for institutional quality. In this respect, our approach emphasises implementing the so-called sunshine principles to improve current methods of evaluation of transparent lobbying.